"Bottom of the Pile": Health Behaviors within the Context of In-work Poverty in North East England. Issue 3 (16th April 2023) - Poulter, Hannah; Eberhardt, Judith; Moore, Helen; Windgassen, Sula
ABSTRACT: In-work poverty (IWP), a growing problem in the United Kingdom, describes being in employment but having financial resources close to thresholds associated with poverty. IWP is associated with poorer health behaviors. We examined why people experiencing IWP may exhibit poorer health behaviors. Experiences of six individuals with whole-household IWP in North East England, were elicited using inductive reflexive thematic analysis with semi-structured interviews. Three themes were generated, showing that IWP impacted on the adoption of healthy behaviors, resulting in an obesogenic environment, particularly for single parents. IWP is a socioeconomic health disparity requiring further exploration.